The Sentinel Stroke National Audit Programme: An improvement tool for community stroke care? - Russell, L. (2024)
Background The Sentinel Stroke National Audit Programme (SSNAP) is an established quality improvement tool for hospital-based stroke care. It is the only national stroke audit that collects data detailing stroke care beyond hospital discharge. However, its role in driving quality improvement in the community setting was unexplored.